2022
DOI: 10.3390/polym14194096
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Modeling of Magnetoactive Elastomers on Different Scales: A State-of-the-Art Review

Abstract: A review of the latest theoretical advances in the description of magnetomechanical effects and phenomena observed in magnetoactive elastomers (MAEs), i.e., polymer networks filled with magnetic micro- and/or nanoparticles, under the action of external magnetic fields is presented. Theoretical modeling of magnetomechanical coupling is considered on various spatial scales: from the behavior of individual magnetic particles constrained in an elastic medium to the mechanical properties of an MAE sample as a whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 172 publications
0
17
0
Order By: Relevance
“…Models focused on explaining the changes in surface roughness of MAEs induced by magnetic fields have identified that strong local deformations are possible due to chaining and clustering of particles. 19,27 Our model treats particles as fixed and does not consider the time evolution of the particle positions (neither due to restructuring 41 nor due to deflection), they only act as a source of force. To obtain a point force per slice, which is a compulsory form of the input for the δ x calculation as we perform it, we simply sum up the contributions of all the particles within a particular slice.…”
Section: Mutual Effect Of Neighbouring Lamellaementioning
confidence: 99%
See 3 more Smart Citations
“…Models focused on explaining the changes in surface roughness of MAEs induced by magnetic fields have identified that strong local deformations are possible due to chaining and clustering of particles. 19,27 Our model treats particles as fixed and does not consider the time evolution of the particle positions (neither due to restructuring 41 nor due to deflection), they only act as a source of force. To obtain a point force per slice, which is a compulsory form of the input for the δ x calculation as we perform it, we simply sum up the contributions of all the particles within a particular slice.…”
Section: Mutual Effect Of Neighbouring Lamellaementioning
confidence: 99%
“…A promising class of smart materials susceptible to magnetic fields are magnetoactive elastomers (MAEs). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] They consist of magnetic microparticles dispersed in an elastomer matrix. A MAE surface can be (micro)structured into various topographies leading to intriguing new functionalities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chougale et al 47 implemented the mean field theory in an invariant based approach to create a constitutive model for anisotropic MAEs. For more details and comparisons between the different modeling strategies, readers can refer to a recent review by Nadzharyan et al 48 An intriguing yet understudied aspect of isotropic MAEs composed of a very soft elastomeric matrix and magnetically soft spherical micro-particles is the phenomenon where the particles rearrange into chain-like structures under a magnetic field. [49][50][51][52][53] This rearrangement of particles can lead to significant changes in the elastic moduli of the material, often spanning several orders of magnitude and changing the isotropic properties to highly anisotropic ones.…”
Section: Introductionmentioning
confidence: 99%